A Study on Immunisation Coverage among Children in Hosakote, Mysuru - Harshini Sure (Journal of Clinical and Diagnostic Research, 2021)
Introduction: Immunisation coverage is a vital strategy adopted by most programs on child survival globally. A robust immunisation coverage program goes a long way in controlling the Vaccine Preventable Disease (VPDs). It is very important to analyse the factors which are detrimental in achieving 100% immunisation among children. Aim: To find the extent of immunisation coverage and to identify the factors for failure of immunisation among children in the rural field practice area of Mysore Medical College and Research Institute, Mysuru. Materials and Methods: A cross-sectional was carried out from November 2019 to January 2020 on children between 0-2 years of age using the World Health Organisation (WHO) thirty clusters sampling method. The sample size was estimated to be 210. Identification of clusters was done as per the WHO manual on 30×7 cluster survey. Interview was conducted using a structured interview format in selected households with study subjects. Data was entered in Microsoft Excel sheet and analysed using chi-square test. Statistical Package for Social Sciences (SPSS) software version 23.0 was used for analysis of data. Results: Among the study participants, 131 (86%) were fully immunised and 29 (14%) were partially immunised (those who did not receive all the due vaccines till two years of age). Religion, educational status of parents and the presence or absence of immunisation card had significant (p-values=0.01, <0.05, <0.05 respectively) association with the immunisation status. The main reasons for partial immunisation were: parents being unaware of the need for returning for subsequent doses 13 (44.8%), fear of side-effects 12 (41.3%), and vaccine not being available 7 (24.1%). Coverage of all individual vaccines among the children (0-2 years) were mostly above 199 (95%). Conclusion: This study observed higher immunisation coverage as compared to that of the national immunisation coverage of 62%. In spite of efforts to increase the immunisation coverage in the country there are regional differences in the extent of this coverage which points to the need for better strategies to tackle this problem.